KEPUASAN, KEPERCAYAAN, KOMITMEN TERHADAP LOYALITAS PELANGGAN PADA AYAM GEPREK BENSU DI PALU - Ermawati, Ermawati (Fakultas Ekonomi Universitas Tadulako, 2019)
This study aims to determine the Effect of Satisfaction, Trust and Commitment on Customer Loyalty in Bensu Geprek Chicken in the City of Palu. This type of research is causal research. The independent variables are satisfaction (X1), trust (X2), commitment (X3). While the dependent variable is customer loyalty (Y). Data collection methods used were observation, interviews and questionnaires. The sampling technique uses accidental sampling with a sample size of 40 respondents. The data analysis method uses multiple linear regression with the help of SPSS 21 for windows software.The results showed that the variables of satisfaction, trust, and commitment have significant results. So it can be concluded that satisfaction, trust and commitment can positively influence customer loyalty at Geprek Bensu in Palu City.